(untitled) (Journal of Engineering, 2025)
This paper proposes a novel control strategy for a Unified Power Quality Conditioner (UPQC) to effectively mitigate voltage and current disturbances in three-phase four-wire (3P-4W) systems. Existing UPQC control approaches often struggle to address unbalanced load conditions, resulting in significant power quality degradation. This research addresses this gap by introducing a fast fuzzy logic (FFZ) controller, which, in comparison to traditional PI controllers, offers enhanced performance in managing DC voltage fluctuations and generating accurate reference currents for the shunt active filter. The proposed FFZ controller effectively minimizes the impact of unbalanced loads on DC voltage, reducing error and improving overall system performance. Simulation results using MATLAB validate the effectiveness of the FFZ controller in reducing total harmonic distortion (THD) and improving transient response, demonstrating its superiority over traditional PI control for unbalanced load scenarios.